Investigation of the Properties of Warm Mix Asphalt Involving Organic Additive - Topal, Ali; Kök, Baha Vural; Kaya, Derya; Şengöz, Burak; Dokandari, Peyman; Yılmaz, Mehmet (Fırat University, 2018)
Demand for sustainable pavements increases day by day in asphalt paving industry. Warm Mix Asphalt (WMA) technology has begun to be an interesting topic for researchers owing to sustainability and environmental issues. Within the scope of this study, the effect of an organic WMA additive was evaluated in terms of mixture characteristics and performance. The fundamental and rheological properties of bitumen samples involving organic WMA additive were determined by conventional bitumen tests and dynamic shear rheometer (DSR). Mixtures modified with organic WMA additives were produced according to Marshall mix design method and the optimum bitumen content of the samples were determined. Following the determination of optimum bitumen content, the effect of the organic WMA additive was investigated in terms of indirect tensile stiffness modulus, fatigue and creep behaviour. Hamburg wheel tracking device was also applied to evaluate the permanent deformation characteristics of WMA mixtures in comparison to Hot Mix Asphalt (HMA) mixtures. The results appraised the effect of the organic WMA additive on rheological and performance characteristics of bituminous mixtures.
Keywords: Engineering; Mühendislik